A personalist approach to public-health ethics - Carlo Petrini; Sabina Gainotti (The World Health Organization, 2008)
First we give an overview of the historical development of public health. Then we present some public-health deontology codes and some ethical principles. We highlight difficulties in defining ethics for public health, with specific reference to three of them that concern: (i) the adaptability to public health of the classical principles of bioethics; (ii) the duty to respect and safeguard the individual while acting within the community perspective that is typical of public health; and (iii) the application-oriented nature of public health and the general lack of attention towards the ethical implications of collective interventions (compared with research). We then mention some proposals drafted from North American bioethics "principles" and utilitarian, liberal and communitarian views. Drawing from other approaches, personalism is outlined as being the theory that offers a consistent set of values and alternative principles that are relevant for public health.